PENGARUH SOSIAL MEDIA DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP MINAT PEMBELIAN PRODUK UKM - Taufik Taufik; Eka Giovana Asti; Iwan Kurniawan; Agus Sudigdo; Irwan Kurniawan (Jurnal Bina Bangsa Ekonomika, 2023)
The application of innovation and adaptation is a necessity for SMEs to continue to exist and develop. This research is intended to analyze how the influence of social media and electronic WOM on the interest in buying SME products. The survey method was used with a questionnaire with a closed question pattern based on 5 Likert scales. A quantitative, population-based approach in the form of consumers buying culinary MSME products online. The author uses a purposive non-random sampling technique with a total of 32 respondents who are online consumers of SME products. Procedures and techniques for data collection based on primary data as the main data, along with other secondary data. Data analysis techniques include validity, reliability, data normality tests, partial correlation tests, coefficient of determination, multiple regression, t tests and F tests. This study shows that partially social media has a significant positive effect on interest in purchasing SME products, as well as partially eWOM positive and significant effect on purchase intention. Simultaneously it was found that social media and eWOM had a significantly positive effect on the intention to purchase SME products